Refugee Telehealth Utilization for Hypertension Management During the COVID-19 Pandemic - Zaid Salameh; Dahlia A. Kaki; Dania Abu Baker; Tarek Hijazi; Job Godino; Job Godino; Tala Al-Rousan (Frontiers Media S.A., 2023)
Objectives: The COVID-19 pandemic limited refugees' access to healthcare. Increased use of telehealth could enable continuity of care but also create barriers to chronic disease management. This study explores refugees' experience with telehealth and hypertension management during the pandemic.Methods: We recruited 109 refugee participants diagnosed with hypertension. We conducted semi-structured interviews about their experience with telehealth during the COVID-19 pandemic. Interviews were transcribed, translated, and data was coded using inductive thematic analysis.Results: 86% used telehealth modalities at least once during the pandemic. Interviews highlighted three main themes: (1) Social isolation worsened mental health, affecting their motivation to manage their blood pressure; (2) telehealth alleviated discontinuity of care but posed logistical and cultural challenges; (3) participants relied on public blood pressure monitors that were not available during the pandemic which affected disease management.Conclusion: Refugees faced challenges managing their hypertension during the COVID-19 pandemic. Virtual community building may alleviate their stress and isolation. Telehealth must be adapted to account for language, cultural, and technological barriers. Communities with hypertension should increase access to personal or public blood pressure monitors.